2016
DOI: 10.1080/21691401.2016.1260579
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of non-irritant microemulsified voriconazole hydrogel system

Abstract: Research was aimed on microemulsion-based hydrogel for voriconazole. Oleic acid and isopropyl myristate as lipid phases; tween 20: tween 80 as surfactants and PEG600 as cosurfactant were selected to formulate voriconazole microemulsions. The promising microemulsions in terms of zeta potential, pH, viscosity, and drug release were selected and developed into hydrogels using carbopol 934. Resulting microemulsion-based hydrogel (MBH) of voriconazole were evaluated for in vitro diffusion and ex vivo permeation. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…However, the oral administration of voriconazole is compromised by complicated pharmacokinetics, notable drug interactions, and relatively significant adverse events [ 5 ]. Furthermore, its intravenous administration is reported to cause heart rhythm problems [ 6 ]. Therefore, a need exists for a topical delivery system to overcome the limitations and enhance the antifungal effect of voriconazole against cutaneous candidiasis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the oral administration of voriconazole is compromised by complicated pharmacokinetics, notable drug interactions, and relatively significant adverse events [ 5 ]. Furthermore, its intravenous administration is reported to cause heart rhythm problems [ 6 ]. Therefore, a need exists for a topical delivery system to overcome the limitations and enhance the antifungal effect of voriconazole against cutaneous candidiasis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This high degree of chemical instability and low solubility of curcumin hinders its oral administration. Although curcumin has a favourable molecular weight (368 Da) for transdermal delivery, other parameters such as its low aqueous solubility and relatively high log P of 3.2 require additional enhancement techniques for skin penetration (10)(11)(12)(13). Numerous studies have aimed at improving curcumin bioavailability and stability by a variety of different approaches including formulation into nanoparticles (14), nanogels (15), microemulsions (16,17), nanofibre transdermal patches (18)(19)(20), micelles (21,22), polymeric conjugates (23,24) or lipid vesicles (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…These results proved that microemulsions had superior fungicidal efficacies due to considerable penetration of the drug into fungal cell membranes. 26 Jadhav et al 27 observed greater activity of fluconazole-loaded microemulsions than of conventional gel formulations and this was attributed to the better diffusion of the drug provided by the presence of surfactants and oil phase. Similarly, El-Hadidy et al 28…”
Section: Atr-ftir Spectroscopymentioning
confidence: 99%